2013
DOI: 10.1371/journal.pone.0059248
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of C-Kit-Targeted Radioimmunotherapy Using 90Y-Labeled Anti-C-Kit Antibodies in a Mouse Model of Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) is an aggressive tumor and prognosis remains poor. Therefore, the development of more effective therapy is needed. We previously reported that high levels of an anti-c-kit antibody (12A8) accumulated in SCLC xenografts. In the present study, we evaluated the efficacy of two antibodies (12A8 and 67A2) for radioimmunotherapy (RIT) of an SCLC mouse model by labeling with the 90Y isotope.Methods 111In- or 125I-labeled antibodies were evaluated in vitro by cell binding, competitive inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…90 Y emits β-particles with a mean emitted energy of 0.9331 MeV, therefore the mean energy emitted per transition was calculated as 1.496 × 10 −13 Gy kg (Bq s) −1 , since 1 eV is equal to 1.602 × 10 −19 J [36]. The calculation procedure of absorbed dose from the biodistribution data was previously described for other radiolabeled antibodies [37]. Briefly, tumor uptake at various time points was plotted against time, and the area under the curve (AUC) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…90 Y emits β-particles with a mean emitted energy of 0.9331 MeV, therefore the mean energy emitted per transition was calculated as 1.496 × 10 −13 Gy kg (Bq s) −1 , since 1 eV is equal to 1.602 × 10 −19 J [36]. The calculation procedure of absorbed dose from the biodistribution data was previously described for other radiolabeled antibodies [37]. Briefly, tumor uptake at various time points was plotted against time, and the area under the curve (AUC) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, within anti-KIT antibodies published or commercially available, of mouse or human KIT specificity, none was described to mediate ADCC or CDC (30, 48) which probably explains the mild toxicity observed in animal models where anti-KIT antibodies were injected (48, 49). Together with the fact that in GIST patients, long term treatment with imatinib does not induce profound hematological toxicity, these observations let anticipate that treatment with KIT specific inhibitory antibodies will not elicit strong toxic secondary effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported pre-clinical data in GIST using naked anti-KIT mAb either competing with SCF (28) or targeting KIT D4 dimerization domain (29). A radiolabelled anti-KIT antibody was also shown to decrease SCLC progression in a mouse model (30). …”
Section: Introductionmentioning
confidence: 99%
“…From the biodistribution data, the tumor and organ time-activity curves were plotted and the AUCs were calculated for representing the residence time of the injected radiocompound. The absorbed doses were calculated according to the formula AUC Â MEEPT Â injected activity (37).…”
Section: Radiation Dosimetrymentioning
confidence: 99%